Urban toll and electric vehicles: The winning ticket for Lyon Metropolitan Area (France). (March 2019) - Souche-Le Corvec, Stéphanie; Mercier, Aurélie; Ovtracht, Nicolas; Chevallier, Amandine
Abstract: The financial situation of the Lyon's public transport network (France) is satisfactory, however its financial structure evolution and the amount of funding requirement revealed the first signs of concern. To get revenues, one of the considered solutions is to implement an urban road toll. Adding to well-known congestion reduction, this solution would get car drivers to contribute better, and it would also lead to reducing pollution and greenhouse gas emissions. In these circumstances, it is necessary to assess the potential effects of implementing this type of pricing solution. In this paper, we propose to evaluate this new pricing measure with respect to several urban indicators (environmental, accessibility, social inequality, public transport performance, public funding requirements). We used the MOSART modelling platform to test several pricing solutions for the Lyon Metropolitan Area based on several possible scenarios for the future (2030). The analysis of our results shows that it is possible to implement an urban toll capable of generating new revenues without increasing inequality. Furthermore, if it associated to the transformation of the fleet of vehicles into electric vehicles, it would also generate positive results regarding CO2 emissions. As a consequence, urban road toll and electric vehicles become the winning ticket for Lyon Metropolitan Area in the future.